Symmetry in Particle Physics - Hnatič, Michal; Antos, Jaroslav; Honkonen, Juha (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
Particle physics is a science about the symmetries of our world. The Standard Model is the fundamental theory of microworld. Particle dynamics in the Standard Model obeys strict symmetry laws with explicit experimental consequences. Priority problems of particle physics based on the Standard Model are more accurate theoretical predictions, experimental measurements and data analysis, proof of existence or non-existence of supersymmetry, top quark properties, Higgs boson, exotic quark states, and physics of neutrinos. In this collection of articles, many of these problems are discussed. We recommend this book for students, graduate students, and scientists working in the field of high energy physics.